Economic sanctions and South Africa - Cooper, John Howard (Rhodes University, Faculty of Commerce, Department of Economics, 1983)
From Introduction: There are few more emotive and contentious contemporary issues of enduring nature than the subject of economic sanctions and South Africa. The controversy surrounding this issue has implications for the structure of international social, political and economic order. The threads of the debate are woven into the historical fabric of the past two decades, during which the acrimony of arguments both for and against sanctions on South Africa has increased. Indeed, for each argument in the debate can be found a counter-argument and "lies, damned lies and statistics" abound. The complex and widespread nature of the question has elevated a practical issue into the realm of theoretical analysis. This thesis is neither purely descriptive nor purely theoretical. It has essentially two focal points, firstly, an attempt at a systematic and reasoned investigation of the many claims and counter-claims, designed to put these arguments into a broad economic framework. There is generally a greater volume of pro-sanctions literature than anti-sanctions literature, some of which is freely available in South Africa, while some is restricted and some not available at all. However, this partial lack of accessibility would seem to pose no material problem of omission: as much of the literature is repetitive, the unavailable material is usually adequately "represented" by material which is available. Also a great part of the literature contains little or no economic analysis since it focuses more on political issues. In this respect the thesis tries to represent the main points of the broad arguments concerned rather than individual nuances and personal viewpoints. It is concerned with sanctions of an economic nature rather than wider sanctions that may affect South African citizens more generally, for example, sport and diplomatic boycotts, bans and restrictions on international travel, etc.
Keywords: Economic sanctions -- South Africa